Editorial, Siddhajyoti Interdisciplinary Journal 2022 (Siddhajyoti Interdisciplinary Journal, 2022)
Research Management Cell (RMC) of Siddajyoti Education Campus (SJEC) has been publishing a research-based academic journal, Siddhajyoti Interdisciplinary Journal (SIJ) since 2020. It aims to encourage teachers to read, write and share their research studies and ideas among teachers, trainers, researchers, policymakers, and practitioners of interdisciplinary subjects (Education, Curriculum, Psychology, EPM, English, Nepali, Mathematics, Science, Social, Population, Economics, Health, Physical Education, business, management, marketing, etc.) in the academic world through publication.In this third volume of Siddhajyoti Interdisciplinary Journal (SIJ), we have included 15 articles following a rigorous peer review and editing process. This volume includes the articles of novice scholars of Nepal from Education, English, Nepali, Mathematics, Science, and Marketing backgrounds. We believe that these articles will be fruitful for the coming generations of multidisciplinary practitioners in Nepal. We request to all valuable readers and scholars contribute by writing for the upcoming issues and reading articles that are published in this volume.We express our gratitude to all authors for their appreciated contributions. Our sincere gratitude goes to all reviewers, who supported the Editorial Team throughout the process. We are equally grateful to the Campus Management Committee of SJEC and RMC for their continuous support to come to this volume in this form. We are also thankful to the designer, Bibek Raj Gautam for the elegant design.Thank you!Editorial TeamSiddhajyoti Interdisciplinary Journal (SIJ)